Jane Addams and the Lost Paradigm of Sociology - Misheva, Vessela (Qualitative Sociology Review, 2019)
The present work is the beginning of a discussion that again addresses the question of Jane Addams’ sociological heritage. That latter is defined as a puzzle which may finally have a solution in that all of the pieces now appear to have been collected. The approach taken to recovering Addams’ identity as a sociologist involves a historico-sociological exploration of the influences upon the formation of her sociological thought, with a focus on Auguste Comte, the Father of Sociology. The article argues that Addams emulated Comte’s scientific mission and took upon herself the task of continuing his project by following another route to the goal. She is thus Comte’s successor, and even rival, insofar as she sought to establish sociology as a science that may be placed in charge of producing knowledge about social life and has the social mission of finding solutions to social problems that politicians proved incapable of tackling. Addams emerges from the discussion as the creator of a sociological paradigm that was dismissed, dismantled, and then lost in the process of the scientific revolution that took place unnoticed after the end of World War I, when the normal period of the scientific development of sociology in America came to an end. The suppression during the 1920s of the type of sociology that Addams developed and adhered to has left sociology in a state of unresolved identity crisis and arrested scientific development.